Confirmatory Factor Structure of the Kaufman Assessment Battery for Children–Second Edition With Preschool Children: Too Young for Differentiation?. (September 2015) - Potvin, Deborah C. H.; Keith, Timothy Z.; Caemmerer, Jacqueline M.; Trundt, Katherine M.
With an age range from 3 to 13 years, the Kaufman Assessment Battery for Children–Second Edition (KABC-II) offers an appealing option for the assessment of cognitive abilities for children. Although independent research has provided evidence of the construct validity of the KABC-II for school-age children, previous studies have rarely included an examination of preschool-age children. This study used confirmatory factor analysis to investigate the structure of the KABC-II in preschool children in relation to the Cattell-Horn-Carroll (CHC) theory of intelligence. By examining competing models based on CHC theory, this study found that the constructs measured by the KABC-II subtests matched those specified within the manual, for children ages 4 through 5. In addition, these results suggested that Gf and Gv are in fact distinct broad abilities for this age group. These findings provide support for differentiated cognitive abilities within young children.